Populasi dan Kondisi Lingkungan Rafflesia arnoldii di Rhino-Camp Resort Sukaraja Atas Taman Nasional Bukit Barisan Selatan (TNBBS) - Delima Nur Ramadhani; Agus Setiawan; Jani Master (Department of Forestry, Faculty of Agriculture, University of Lampung, 2017)
Bukit Barisan Selatan National Park is the habitat of endangerd species rafflesia (Rafflesia arnoldii) which parasiting on Tetrastigma sp. One of it, concentrated in Rhino Camp TNBBS which situated nearby Sanggi-Bengkunat avenue which high potentially to be suppressed. Obviously, these could trigger a high distraction which could affect on its environmental condition and population changing. The purpose of the study were to recognized the populations and environmental conditions of rafflesia in Rhino CampSukaraja Atas Resort, TNBBS. The research conducted in February 2016 used survey method. The study showed there was 49 idividual rafflesia, under two conditions: 67% alive and 33% already died. Its ambient conditions based on abiotics conditions has temperature range about 25-290 C, under medium canopy density (32-68%), humidity about 95%, soilacidity catagorized as acid (pH= 5,5), slopes included as approximated steep (30-45%), elevation about 490-558 meters above sea level and situated on ±7 m from the nearest water sources. In addition, its biotics components consist of Tetrastigma lanceolarium; defined as rafflesia’s host plant. While its pollinator was predicted mostly from Diptera: Lucilia sp, Sarcopaga sp and Dorsophila spp and Caliphora vomitoria, Hymenoptera: Lasius fuliginosus, also Coleoptera: Staphilinidae sp. Living presentage of rafflesia indicate thatRhino camp TNBBS is sustainable habitat for rafflesia. Keywords: envirnoment, Bukit Barisan Selatan National Park, population, Rafflesia arnoldii